Expression-Linked Patterns of Codon Usage, Amino Acid Frequency, and Protein Length in the Basally Branching Arthropod Parasteatoda tepidariorum. (26th March 2016) - Whittle, Carrie A.; Extavour, Cassandra G.
Abstract: Spiders belong to the Chelicerata, the most basally branching arthropod subphylum. The common house spider, Parasteatoda tepidariorum, is an emerging model and provides a valuable system to address key questions in molecular evolution in an arthropod system that is distinct from traditionally studied insects. Here, we provide evidence suggesting that codon usage, amino acid frequency, and protein lengths are each influenced by expression-mediated selection in P. tepidariorum . First, highly expressed genes exhibited preferential usage of T3 codons in this spider, suggestive of selection. Second, genes with elevated transcription favored amino acids with low or intermediate size/complexity (S/C) scores (glycine and alanine) and disfavored those with large S/C scores (such as cysteine), consistent with the minimization of biosynthesis costs of abundant proteins. Third, we observed a negative correlation between expression level and coding sequence length. Together, we conclude that protein-coding genes exhibit signals of expression-related selection in this emerging, noninsect, arthropod model.